Analisis Pengaruh Motivasi, Disiplin Kerja, dan Etos Kerja terhadap Kinerja Personil melalui Kinerja Tugas pada Salah Satu Satuan Kerja Kepolisian di Jakarta - Deby Saputra; Hamsinah B; Rahmi Hermawati (Jurnal EMT KITA, 2026)
The purpose of this study was to examine and analyze the effects of motivation, work discipline, and work ethic on task implementation and performance, as well as the effect of task implementation on the performance of personnel in a special police work unit in Jakarta. This study was designed using a descriptive method with a quantitative approach employing the Partial Least Squares Structural Equation Modeling (PLS-SEM) technique. The population consisted of 328 personnel from a special police work unit in Jakarta. The sampling technique used was probability sampling with a simple random sampling approach. The sample size was determined using the Slovin formula, resulting in 180 respondents. The findings indicate that motivation, work discipline, and work ethic have a positive and significant effect on task implementation. Motivation and work ethic also have a positive and significant effect on performance, while work discipline has a positive but insignificant effect on performance. Furthermore, task implementation has a positive and significant effect on performance. Therefore, task implementation serves as an intervening variable in the relationship between motivation, work discipline, and work ethic and personnel performance.